2021
DOI: 10.3390/agronomy11122482
|View full text |Cite
|
Sign up to set email alerts
|

Lead-Tolerant Bacillus Strains Promote Growth and Antioxidant Activities of Spinach (Spinacia oleracea) Treated with Sewage Water

Abstract: Irrigation with sewage-contaminated water poses a serious threat to food security, particularly in developing countries. Heavy metal tolerant bacteria are sustainable alternatives for the removal of wastewater contaminants. In the present study, four lead (Pb)-tolerant strains viz. Bacillus megaterium (N8), Bacillus safensis (N11), Bacillus sp. (N18), and Bacillus megaterium (N29) were inoculated in spinach and grown in sewage water treated earthen pots separately and in combination with canal water. Results s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 49 publications
(54 reference statements)
1
1
0
Order By: Relevance
“…The present study is in close confirmation with the work performed by Najm‐ul‐Seher et al (2021) where they reported that the inoculation of the strain Bacillus sp. (N18) caused a considerable increase in shoot length, root length, shoot fresh weight, root fresh weight, shoot dry weight, root dry weight, and leaf area of spinach plants when compared to the uninoculated control of sewage water‐treated plants.…”
Section: Discussionsupporting
confidence: 93%
“…The present study is in close confirmation with the work performed by Najm‐ul‐Seher et al (2021) where they reported that the inoculation of the strain Bacillus sp. (N18) caused a considerable increase in shoot length, root length, shoot fresh weight, root fresh weight, shoot dry weight, root dry weight, and leaf area of spinach plants when compared to the uninoculated control of sewage water‐treated plants.…”
Section: Discussionsupporting
confidence: 93%
“…Fifty seeds of both species were sown in each pot. Four sets were prepared for both seeds: (i) Control (non-inoculated) (ii) Inoculated with lead resistant bacteria [T 1 ] (10 6 cfu/gm of soil) (iii) Inoculated with resistant bacteria and 1000ppm Pb(NO 3 ) 2 [T 2 ] (iv) Soil with 1000ppm Pb(NO 3 ) 2 [T 3 ] according to the method described 12 and modified to prepare the mentioned sets. All pots were allowed to grow for 4 weeks and were observed periodically for root, shoot and leaf development and results were recorded.…”
Section: Pot Experiments To Determine Plant Growth Promoting Propertiesmentioning
confidence: 99%